Effects of Website Interactivity on Skin Cancer-Related Intentions and User Experience: Factorial Randomized Experiment - Niu, Zhaomeng; Willoughby, Jessica Fitts; Coups, Elliot J; Stapleton, Jerod L (JMIR Publications, 2021)
BackgroundDigital media technologies provide users with the ability to interact with content and to receive information based on their preferences and engagement. ObjectiveWe used skin cancer and sun protection as a health topic to explore how modality interactivity, interface tools that afford users greater activity, resulting in greater depth and breadth of mentally representing and experiencing mediated content, and message interactivity, the extent to which the system allows users to exchange messages back and forth on health websites, influenced users' attitudes, knowledge, behavioral intentions, and experience. MethodsWe employed a 2×2 (modality interactivity: high vs low; message interactivity: high vs low) between-subject online experiment for which 4 websites were created. Participants (n=293) were recruited using Amazon Mechanical Turk and randomly assigned into to 1 of 4 conditions. After browsing the website, participants completed an online survey regarding their experience and cognitive perceptions. General linear models and path analysis were used to analyze the data. ResultsBoth modality interactivity (P=.001) and message interactivity (P<.001) had an impact on intention to use sun protection. Attitudes toward health websites and perceived knowledge mediated the effects of modality interactivity and message interactivity on sun protection use intention, individually. Participants in the high modality interactivity and high message interactivity condition felt more satisfied (P=.02). Participants in the low message interactivity condition had more interest in the experience with health websites than participants in the high message interactivity condition (P=.044). ConclusionsFindings suggested that modality interactivity influenced intention to use sun protection directly as well as via attitudes toward the websites. Message interactivity impacted intention to use sunscreen directly and also through perceived knowledge. Implications for designing health websites and health intervention content are discussed.